Prognostic Impact of 18F-FDG PET/CT in Patients With Aggressive B-Cell Lymphoma Treated With Anti-CD19 Chimeric Antigen Receptor T Cells. (August 2021) - Sesques, Pierre; Tordo, Jérémie; Ferrant, Emmanuelle; Safar, Violaine; Wallet, Florent; Dhomps, Anthony; Brisou, Gabriel; Bouafia, Fadhela; Karlin, Lionel; Ghergus, Dana; Golfier, Camille; Lequeu, Helène; et al.
Abstract : Purpose of the Report: We aimed to evaluate the role of 18 F-FDG PET/CT in predicting patient outcome following chimeric antigen receptor T (CAR T) cells infusion in aggressive B-cell lymphoma. Methods: 18 F-FDG PET/CT data before leukapheresis, before CAR T-cell infusion and 1 month (M1) after CAR T-cell infusion, from 72 patients were retrospectively analyzed. SUVmax, total lesion glycolysis (TLG), metabolic tumor volume (MTV), and parameters describing tumor kinetics were calculated for each 18 F-FDG PET/CT performed. The aim was to evaluate the prognostic value of 18 F-FDG PET/CT metabolic parameters for predicting progression-free survival (PFS) and overall survival (OS) following CAR T-cell therapy. Results: Regarding PFS, [INCREMENT]MTV pre-CAR and [INCREMENT]TLG pre-CAR were found to be more discriminating compared with metabolic parameters at preinfusion. Median PFS in patients with a [INCREMENT]MTV pre-CAR of less than 300% was 6.8 months (95% confidence interval [CI], 2.8 months to not reached) compared with 2.8 months (95% CI, 0.9–3.0 months) for those with a value of 300% or greater ( P = 0.004). Likewise, median PFS in patients with [INCREMENT]TLG pre-CAR of less than 420% was 6.8 months (95% CI, 2.8 months to not reached) compared with 2.7 months (95% CI, 1.3–3.0 months) for those with a value of 420% or greater ( P = 0.0148). Regarding OS, metabolic parameters at M1 were strongly associated with subsequent outcome. SUVmax at M1 with a cutoff value of 14 was the most predictive parameter in multivariate analysis, outweighing other clinicobiological variables ( P < 0.0001). Conclusions: Disease metabolic volume kinetics before infusion of CAR T cells seems to be superior to initial tumor bulk itself for predicting PFS. For OS, SUVmax at M1 might adequately segregate patients with different prognosis. Abstract : Supplemental digital content is available in the text.